Persistence in the performance of South African unit trusts - J. F.C. Von Wielligh; E. V.D.M. Smit (South African Journal of Business Management, 2000)
The persistence of performance of the General Equity Unit Trusts and All Unit Trusts that traded in South Africa during the period January 1988 to December 1997 and January 1993 to December 1997, is analysed using three models of performance measurement, namely the Capital Asset Pricing Model, a two-factor Arbitrage Pricing Theory model and a three-factor Arbitrage Pricing Theory (APT) model developed in this study. The Capital Asset Pricing Model does not explain the relative returns of the different portfolios. Both APT models account for almost all of the cross-sectional variation in expected returns. It is shown that there is evidence of both short-term and long-term persistence in performance of South African unit trusts. It appears that the worst performing unit trust portfolio tends to stay the worst performer. The portfolio of unit trusts with an average monthly return may eventually become the top performing portfolio, while the top performer over time tends to becomes an average performing portfolio.
Keywords: 650